Planning in Norway 1947-1956 - Bjerve, Petter Jakob (Amsterdam : North-Holland Pub Co., 1959)
This volume is comprehensive account the planning process in Norway. It is divided into 10 parts: the background; the method and procedure of planning; interpretation of deviations between national budgets and accounts; projections of production; the export and import plans; projections of consumption; the investment plans; the building programmes; the main objectives for allocation of resources; and an appraisal.
Includes bibliographical references and index.
lje 16/10/2018
Loans
Keywords: Economic planning; Economic policy; Norway